Longevity of immediate rehabilitation with direct metal-wire reinforced composite fixed partial dentures. Issue 10 (October 2022) - Wierichs, R.J.; Weilenmann, W.; Jeganathan, S.; Perrin, P.
Abstract: Objectives: This study aimed to analyze the longevity of direct metal-wire reinforced composite fixed partial dentures (MRC-FPD) and factors influencing their survival and success. Methods: Within one private practice 513 MRC-FPD were directly applied. The preparation of a proximal cavity in abutment teeth was not limited. MRC-FPD were reinforced by one to three metal-wires. At the last follow-up MRC-FPD were considered successful, if they were still in function without any need of therapy. MRC-FPD were considered as survived, if they were repaired or replaced. Multi-level Cox proportional hazard models were used to evaluate the association between clinical factors and time. Results: Mean follow-up period (range) was 59(2−249) months. Seventy-three bridges did not survive (cumulative survival rate(CSR):86%) and further 129 bridges had received a restorative follow-up treatment (CSR:61%). AFR was 2.2% for survival and 8.6% for success. In multivariate analysis MRC-FPD with> 1 wire showed a up to 2.3x higher failure rate than MRC-FPD with one wire(p ≤ 0.023). Dentist's experience in designing MRC-FDP (p ≤ 0.017), patient's caries risk (p ≤ 0.040) and bruxism (p = 0.033) significantly influenced the failure rate: the more experience, the lower caries risk and bruxism, the lower the failure rate. Significance: For directly prepared metal-wire reinforced composite bridges high survival and moderate success rates were observed. MRC-FPD might, thus, be an immediate, short- and medium-term solution for replacing missing teeth. However, several factors on the levels of practice (dentist's experience in designing MRC-FDP), patient (bruxism, caries risk) and restoration (number of wires) were identified as significant predictors for the failure rate. The study was registered in the German Clinical Trials Register (DRKS-ID: DRKS00021576). Highlights: Analysis of direct metal-reinforced composite bridges (MRC-FDP) for up to 20years. Directly prepared MRC-FDP showed high survival and moderate success rates. Dentist's experience with MRC-FDP had a positive influence on survival and success. Patient's caries risk and bruxism significantly influenced the failure rate.